Análise numérica transiente térmica estrutural das tensões residuais em vasos de pressão cilíndricos submetidos a reparo por solda de acordo com a norma ASME PCC-2-2015 - Almeida, Jayann Ismar Lira (2017)
This thesis aims to determine the residual stresses of cylindrical pressure vessels submitted to weld repairs using the standard ASME PCC-2-2015 via numerical analysis. The residual stress analysis methods are, in most cases, costly and time consuming, especially in large structures such as pressure vessels, and it is important to observe the behavior of these stresses mainly in the thermally affected areas. In welding repair, the sleeve is attached to the pressure vessel through two longitudinal welds and two transverse welds. Modeling of the pressure vessel, the repair and the welds according to the norm was carried out, and the finite element mesh quality was analyzed. The welding parameters were adopted with what happens in practice, and with this the temperature and heat flux distribution were obtained. The objectives were to analyze the longitudinal, tangential and von Mises residual stresses in the regions of the weld, pressure vessel and repair during the welding period, and to verify the behavior of these stresses after the cooling period by the Finite Element Method. The deformations in the repair after welding were analyzed to calculate the retraction pressure. This work shows that numerical analysis can be used with efficiency and objectivity in situations with residual stress by weld.